Peran Wawasan Nusantara dalam Mencegah Konflik Budaya - Klau, Anastasia Saputri; Kollo, Fredik Lambertus; Kamlasi, Anjulin Yonathan; Tulit, Rosalinda Ina; Banase, Yohanes P. (Universitas Muhammadiyah Ponorogo, 2026)
This study discusses the function of the Archipelagic Concept as an instrument for preventing conflicts arising from cultural differences in Indonesia. With its multicultural society, characterised by hundreds of ethnic groups and diverse regional languages, Indonesia faces significant challenges in maintaining national unity amid such diversity. Intercultural friction often arises due to differences in value systems, conflicting interests, and a lack of national awareness. This study uses a qualitative descriptive approach, utilising literature reviews from various relevant legal documents and literature. The findings show that the application of the principles of Wawasan Nusantara, which include national unity, mutual respect, and equitable welfare, can strengthen national cohesion and anticipate cross-cultural conflicts. Recognition of customary legal systems and the application of local values have been shown to increase the credibility of legal institutions while maintaining balance in community life. However, its implementation still faces obstacles such as limited public knowledge of this concept and the impact of globalisation. Therefore, strengthening efforts are needed through an education system that respects diversity and public policies that prioritise the principle of social justice